Hydrophilic intraocular lens material as well as preparation method and application thereof

By using high-water content intraocular lens materials with components such as acrylate monomers, ultraviolet absorbers and 2-methacryloyloxyethylphosphocholine, the whitening problems caused by insoluble salt deposition and temperature changes in existing materials are solved, and higher biocompatibility, flexibility and long-term stability are achieved.

CN119798527APending Publication Date: 2025-04-11GAUSH TELEON LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411986733.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

During the use of existing hydrophilic intraocular lens materials, there are whitening phenomena caused by insoluble salt deposition and temperature changes, which affect their long-term stability and visual effects.

Method used

By simplifying the raw material formulation, a high moisture content and low viscosity intraocular lens material is prepared by simplifying the raw material formula and using acrylate monomer, ultraviolet absorber and 2-methacryloyloxyethylphosphate as main components, which significantly reduces the risk of deposition of insoluble salts and the opacification caused by temperature changes.

Benefits of technology

This material significantly improves the deposition properties of hard-soluble salts and transparency under temperature changes, enhances biocompatibility and flexibility, simplifies production processes, and has better clinical application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005222762270000201
    Figure BDA0005222762270000201
Patent Text Reader

Abstract

The invention provides a hydrophilic intraocular lens material as well as a preparation method and application thereof. The hydrophilic intraocular lens material is prepared from the following raw materials: an acrylate monomer, an ultraviolet absorbent, 2-methacryloyloxyethyl phosphorylcholine and an initiator, the formula of the raw materials is simplified, and the acrylate monomer, the ultraviolet absorbent and the 2-methacryloyloxyethyl phosphorylcholine are used as main components; the composition of the preparation raw materials is simple, no extra hydrophobic acrylate monomer is needed, the viscosity of the material is remarkably reduced, the flexibility is improved, and the use of hydrophobic components is reduced, so that the risk of deposition of insoluble salt is reduced. The invention further provides a preparation method and application of the hydrophilic intraocular lens material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of biomedical polymer materials, and in particular relates to a hydrophilic artificial lens material and a preparation method and application thereof. Background Art

[0002] Intraocular lenses are an indispensable material in ophthalmic surgery and are widely used to treat eye diseases such as cataracts and refractive errors. According to their purpose of use, intraocular lenses can be divided into two types: one is an aphakic intraocular lens used to treat cataracts as a substitute for the cloudy natural lens; the other is a phakic intraocular lens used to correct refractive errors such as myopia, hyperopia and presbyopia by implanting the intraocular lens into the eye to adjust the refraction of light and improve vision.

[0003] At present, the intraocular lens materials used in the market are mainly divided into hydrophilic materials and hydrophobic materials. Compared with hydrophobic materials, hydrophilic materials have better biocompatibility and can reduce the inflammatory response in the eye after implantation, thereby ensuring the long-term stability and function of the implant. In addition, hydrophilic materials usually have better folding properties, which makes it easier to fold and inject during surgery, with smaller implantation incisions, reducing the difficulty of surgery and the risks during implantation. Although hydrophilic materials have obvious advantages in performance, there are still some technical difficulties in existing hydrophilic intraocular lens materials, which affect their clinical application effects. First, the problem of insoluble salt deposition, such as calcium salt deposition, is one of the main challenges of current hydrophilic intraocular lens materials. Insoluble salt deposition will cause deposits on the surface of the lens. Over time, the deposits will gradually accumulate, eventually causing the intraocular lens to lose transparency, affecting the patient's vision, and even causing the implant to fail. Studies have shown that the occurrence of calcium salt deposition may be related to the microstructure and chemical composition of the surface of hydrophilic materials. This problem, especially if it is not resolved for a long time after implantation, may have a serious impact on the patient's visual quality. Secondly, another problem with hydrophilic intraocular lens materials is the whitening of the lens caused by temperature changes. In high-latitude areas, when hydrophilic intraocular lenses are transplanted into the human body in a cold environment, the physical properties of the hydrophilic material change due to the higher intraocular temperature compared to the storage environment temperature, which can easily lead to opacification of the lens surface. This phenomenon not only affects the optical properties of the lens after implantation, but may also have an adverse effect on the patient's postoperative recovery. Especially in cold seasons, the temperature adjustment time of artificial lenses is longer, and more time is needed to adapt to the intraocular environment. This is an urgent problem to be solved for patients who need to quickly restore their vision.

[0004] In order to overcome these problems, the hydrophilic intraocular lens in the prior art is usually prepared by combining materials such as hydrophobic acrylic monomers, acrylate crosslinkers and ultraviolet absorbers. Through the precise ratio of these components, the transparency, biocompatibility and folding and injection performance of the intraocular lens can be improved to a certain extent. However, the current hydrophilic intraocular lens materials, due to the addition of a large amount of hydrophobic monomers (at least more than 5wt%), on the one hand, will cause the modulus or hardness of the material to increase, which may cut the intraocular tissue when implanted into the eye, and on the other hand, it will cause the viscosity of the material to increase, which will cause the risk of adhesion of the iris after implantation into the eye, and the risk of deposition of iris pigments. Secondly, the addition of a large amount of hydrophobic monomers will still lead to the opacification phenomenon caused by the temperature of the material. Although these materials have played a positive role in improving the performance of intraocular lenses, the problem of insoluble salt deposition still exists and cannot be completely eliminated. Therefore, it is urgent to develop a new intraocular lens material that can significantly improve its resistance to insoluble salt deposition and improve transparency under temperature changes. By optimizing the chemical structure, surface characteristics and physical properties of the material, and solving the problems of calcium salt deposition and whitening encountered by existing materials during use, not only can the long-term stability of artificial lenses be improved, but also the patient's visual quality and postoperative rehabilitation effect can be improved. Summary of the invention

[0005] The present invention aims to solve at least one of the above technical problems existing in the prior art. To this end, the present invention provides a hydrophilic intraocular lens material, which can significantly improve the resistance to insoluble salt deposition and improve the transparency under temperature changes.

[0006] The invention also provides a method for preparing a hydrophilic intraocular lens material.

[0007] The invention also provides the use of the hydrophilic intraocular lens material in preparing an aphakic intraocular lens or a phakic intraocular lens.

[0008] The first aspect of the present invention provides a hydrophilic intraocular lens material, wherein the raw materials for preparing the hydrophilic intraocular lens material include an acrylate monomer, an ultraviolet absorber, 2-methacryloyloxyethyl phosphorylcholine and an initiator.

[0009] One of the technical solutions of the present invention regarding the artificial lens material has at least the following beneficial effects:

[0010] The artificial lens material of the present invention uses acrylate monomer, ultraviolet absorber and 2-methacryloyloxyethyl phosphorylcholine as main components by simplifying the raw material formula, and the raw material composition is simple, without additional hydrophobic acrylate monomer, which significantly reduces the viscosity of the material, reduces the risk of iris adhesion and pigment deposition, and is conducive to obtaining a material with a high water absorption expansion coefficient. The introduction of a higher content of 2-methacryloyloxyethyl phosphorylcholine enhances the hydrophilicity and resistance to insoluble salt deposition of the material, improves biocompatibility and transparency, and at the same time, a higher content of ultraviolet absorber effectively protects the eyes from ultraviolet damage. Further, by adjusting the refractive index of the material by adjusting the content of ultraviolet absorber, a material with high water content and high refractive index can be prepared, which is conducive to the artificial lens design to achieve a thinner effect under the same optical focal power conditions, and is conducive to the push injection implantation of the product into the eye, without the need to use an additional high-content hydrophobic monomer to adjust the refractive index of the material. The acrylate monomer used in the present invention is a hydrophilic alkyl acrylate monomer containing only hydroxyl hydrophilic functional groups, does not contain other elements except C, O and H, and avoids the risk of biological toxicity of using monomers containing other heteroatoms. In addition, the material is not prone to whitening under high temperature differences. This material not only improves the long-term stability of artificial lenses, but also simplifies the production process and has better clinical application prospects.

[0011] According to some embodiments of the present invention, the content of the acrylate monomer in the preparation raw material is 79.9 to 92 wt % by mass.

[0012] In the intraocular lens material of the present invention, the content of acrylate monomer is 79.9-92wt%, which ensures the high water content, mechanical strength, high water absorption expansion coefficient and stability of the material, while optimizing the softness and folding performance, and facilitating surgical operation. The high content of acrylate monomer reduces the interference of other components, enhances the transparency and resistance to insoluble salt deposition of the material, and ensures its long-term stability and use effect in the eye.

[0013] According to some embodiments of the present invention, the acrylate monomer includes 2-hydroxyethyl methacrylate.

[0014] As an acrylate monomer, 2-hydroxyethyl methacrylate can significantly enhance the hydrophilicity, transparency and flexibility of intraocular lenses and improve their biocompatibility. The hydrophilicity of 2-hydroxyethyl methacrylate helps the material maintain hydration, improves transparency and reduces the risk of insoluble salt deposition, while improving compatibility with ocular tissues and reducing postoperative discomfort. It also improves the softness and folding properties of the material, facilitates surgical operations, and enhances the structural stability of the material, ensuring stability and visual effects after long-term implantation.

[0015] According to some embodiments of the present invention, the content of the ultraviolet absorber in the preparation raw material is 2.9-5wt% by mass.

[0016] The ultraviolet absorber accounts for 2.9-5wt% in the artificial lens material of the present invention, which can effectively absorb and block ultraviolet rays, protect the eyes from damage caused by ultraviolet rays, prevent eye diseases such as cataracts, and delay eye aging. The ultraviolet absorber within this concentration range can also maintain the transparency and optical stability of the lens, ensure the visual effect after long-term implantation, and will not affect other properties of the material. By introducing a higher mass fraction of ultraviolet absorber, the refractive index of the material can be significantly improved, and the effect on the water content of the material is small, so that the material can achieve a high water content while obtaining a higher refractive index performance. The ultraviolet absorber is an ultraviolet absorber containing an acrylate or methacrylate functional group, and commonly used ones are ultraviolet absorbers containing benzophenones, azoles and oxazine.

[0017] According to some embodiments of the present invention, the ultraviolet absorber includes 2-hydroxy-4-(methacryloyloxy)benzophenone or 2-(4-benzoyl-3-hydroxyphenoxy)ethyl 2-acrylate.

[0018] According to some embodiments of the present invention, the content of 2-methacryloyloxyethyl phosphorylcholine in the preparation raw material is 4.9-15 wt % by mass.

[0019] The content of 2-methacryloyloxyethyl phosphorylcholine in the artificial lens material of the present invention is 4.9-15wt%, which can significantly enhance the hydrophilicity and resistance to insoluble salt deposition of the material, reduce the risk of calcium salt deposition, and maintain the long-term transparency of the lens. At the same time, 2-methacryloyloxyethyl phosphorylcholine improves biocompatibility, reduces immune rejection, and enhances affinity with intraocular tissues. In addition, the addition of 2-methacryloyloxyethyl phosphorylcholine can also adjust the water content of the material according to demand to balance the performance of the introduction of a higher content of ultraviolet absorber, and adjust the water absorption expansion coefficient of the material, thereby improving the softness and operability of the material, facilitating surgical operations, and improving postoperative effects and comfort.

[0020] According to some embodiments of the present invention, the content of the initiator in the preparation raw material is ≥ 0.01 wt %, and the rate of the material polymerization reaction can be adjusted by adjusting the initiator content as required.

[0021] According to some embodiments of the present invention, the initiator includes at least one of azobisisobutyronitrile and azobisisoheptanenitrile.

[0022] According to some embodiments of the present invention, the water content of the intraocular lens material is ≥ 30 wt %.

[0023] Intraocular lenses with a water content of ≥30wt% can enhance the hydrophilicity, transparency and flexibility of the material, improve biocompatibility and comfort, while helping to reduce the deposition of insoluble salts and prolong its stability and service life in the eye.

[0024] According to some embodiments of the present invention, the hydration expansion coefficient of the intraocular lens material is ≥1.13, and more preferably ≥1.15. The hydration expansion coefficient of the currently known hydrophilic intraocular lens materials is usually <1.3, the molecular chains of the material are more compact, the elastic modulus of the material is higher, and the low expansion coefficient is not conducive to the permeability and migration of ions in the intraocular saline solution, resulting in an increased risk of insoluble salt deposition. The material absorbs water and swells, and a higher water absorption expansion coefficient gives the liquid a larger space to migrate in the material, which is more conducive to the permeability and migration of physiological ocular solutions in the body fluids of the eye after implantation in the eye, reducing the risk of insoluble salt deposition.

[0025] Intraocular lenses with a hydration expansion coefficient ≥1.13, especially those with a hydration expansion coefficient ≥1.15, can provide a lower elastic modulus, better flexibility, and are more conducive to the migration of intraocular fluid ions, reducing the risk of insoluble salt deposition and improving surgical operability and postoperative comfort.

[0026] The whitening phenomenon of the material under temperature changes is also a manifestation of the low exchange rate of the reaction hydration solution in the material. The ion diffusion is slow. After implantation in the eye, in some patients, there are ions such as calcium that are easy to form precipitated salts to form an oversaturated concentration, resulting in a higher risk of deposition. The material of the present invention does not contain an additional high content of hydrophobic monomers, so the material has strong hydrophilicity inside and outside, which is more conducive to the diffusion of the solution, is less sensitive to temperature differences, and is not easy to cause whitening.

[0027] According to some embodiments of the present invention, the elongation at break of the intraocular lens material is ≥200wt%, preferably ≥300%, which can provide better flexibility, fracture resistance and adaptability, improve operability during surgery, enhance intraocular stability, reduce postoperative discomfort, and improve the durability and long-term biocompatibility of the intraocular lens.

[0028] According to some embodiments of the present invention, the elastic modulus of the artificial lens material is 0.15-0.35 MPa. An excessively large elastic modulus will result in a large deviation from the mechanical characteristics of the physiological tissues in the eye, causing a foreign body sensation in the intraocular tissues and a risk of cutting the intraocular tissues. The elastic modulus of the currently known hydrophilic artificial lens materials is generally greater than 0.5 MPa, and more often ≥ 1 MPa. The elastic modulus of the artificial lens material is 0.15-0.35 MPa, which is closer to the elastic modulus of the intraocular tissues. After implantation in the eye, it can provide better biocompatibility, comfort and operability, ensure long-term stability and transparency in the eye, reduce postoperative discomfort, and improve the success rate of surgery and the durability of the material.

[0029] According to some embodiments of the present invention, the preparation raw materials are 2-hydroxyethyl methacrylate, 2-hydroxy-4-(methacryloyloxy)benzophenone, 2-methacryloyloxyethyl phosphorylcholine and azobisisobutyronitrile, wherein the 2-hydroxyethyl methacrylate accounts for 91.99wt% of the preparation raw materials, the 2-hydroxy-4-(methacryloyloxy)benzophenone accounts for 2.99wt% of the preparation raw materials, the 2-methacryloyloxyethyl phosphorylcholine accounts for 4.99wt% of the preparation raw materials, and the azobisisobutyronitrile accounts for 0.01wt% of the preparation raw materials.

[0030] According to some embodiments of the present invention, the preparation raw materials are 2-hydroxyethyl methacrylate, 2-(4-benzoyl-3-hydroxyphenoxy)ethyl 2-acrylate, 2-methacryloyloxyethyl phosphorylcholine and azobisisobutyronitrile, wherein the 2-hydroxyethyl methacrylate accounts for 85.99wt% of the preparation raw materials, the 2-(4-benzoyl-3-hydroxyphenoxy)ethyl 2-acrylate accounts for 3.99wt% of the preparation raw materials, the 2-methacryloyloxyethyl phosphorylcholine accounts for 9.99wt% of the preparation raw materials, and the azobisisobutyronitrile accounts for 0.02wt% of the preparation raw materials.

[0031] According to some embodiments of the present invention, the preparation raw materials are 2-hydroxyethyl methacrylate, 2-hydroxy-4-(methacryloyloxy)benzophenone, 2-methacryloyloxyethyl phosphorylcholine and azobisisobutyronitrile, the 2-hydroxyethyl methacrylate accounts for 79.99wt% of the preparation raw materials, the 2-hydroxy-4-(methacryloyloxy)benzophenone accounts for 4.99wt% of the preparation raw materials, the 2-methacryloyloxyethyl phosphorylcholine accounts for 14.99wt% of the preparation raw materials, and the azobisisobutyronitrile accounts for 0.05wt% of the preparation raw materials.

[0032] The second aspect of the present invention provides a method for preparing the intraocular lens material of the first aspect of the present invention, comprising the steps of mixing various preparation raw materials and then subjecting them to polymerization reaction.

[0033] A technical solution in the method for preparing an artificial lens material of the present invention has at least the following beneficial effects:

[0034] The preparation method of the present invention does not require expensive equipment and complex process control, has undemanding reaction conditions, requires a small number of raw materials that are easily available, has low production costs, and is easy to industrialize.

[0035] According to some embodiments of the present invention, the polymerization reaction temperature is 25-120°C.

[0036] According to some embodiments of the present invention, the polymerization reaction time is 12 hours to 7 days.

[0037] The third aspect of the present invention provides use of the hydrophilic intraocular lens material of the first aspect of the present invention in preparing an aphakic intraocular lens or a phakic intraocular lens.

[0038] The hydrophilic intraocular lens material of the present invention has excellent biocompatibility, optical properties and long-term stability when used in aphakic or phakic intraocular lenses. It can effectively reduce salt deposition and ultraviolet damage, improve postoperative comfort and surgical operability, and extend service life. The high hydrophilicity and moderate refractive index of the material enable it to still have good optical effects under high water content, and at the same time, it is low-cost and easy to industrialize, and has broad clinical application prospects. DETAILED DESCRIPTION

[0039] The following are specific embodiments of the present invention, and the technical solutions of the present invention are further described in conjunction with the embodiments, but the present invention is not limited to these embodiments.

[0040] In a first aspect, some embodiments of the present invention provide an artificial lens material, wherein the raw materials for preparing the material include an acrylate monomer, an ultraviolet absorber, 2-methacryloyloxyethyl phosphorylcholine and an initiator.

[0041] The artificial lens material of the present invention is composed of three main components: acrylate monomer, ultraviolet absorber, and 2-methacryloyloxyethyl phosphorylcholine. The raw material composition is simple, and there is no additional hydrophobic acrylate monomer, which reduces the viscosity of the material, improves the softness of the material, and reduces the risk of insoluble salt deposition. Compared with traditional artificial lens materials, the raw materials for preparation are optimized. This optimization not only simplifies the raw material ratio, but also brings some important beneficial effects, as follows:

[0042] 1. Reduced use of hydrophobic acrylate monomers, reducing the viscosity of the material. In traditional hydrophilic intraocular lens materials, some hydrophobic acrylate monomers, such as methyl acrylate, are usually added to improve the mechanical strength and folding performance of the material. However, these hydrophobic components will increase the viscosity of the material to a certain extent, affecting its softness and operability. In the raw material formula used in the present invention, no hydrophobic acrylate monomer is added, thereby reducing the viscosity of the material, making the material smoother during the preparation process, and easier to handle and shape. The direct benefits brought about by this change are:

[0043] Improved softness: The material becomes softer, which helps to fold and push more smoothly during the operation, thereby reducing the difficulty of the operation and improving the success rate of the operation.

[0044] Improved operability: Reduced viscosity makes it easier to accurately place the intraocular lens material during intraocular manipulation, reducing potential risks during surgery.

[0045] 2. Reduced the risk of deposition of sparingly soluble salts (such as calcium salts). The problem of calcium salt deposition has always been one of the difficulties of hydrophilic intraocular lens materials. The deposition of sparingly soluble salts will not only cause the surface of the intraocular lens to lose transparency and affect the patient's vision, but in severe cases it will even lead to loss of lens function. Traditional intraocular lens materials often use certain hydrophobic components to enhance the mechanical properties and foldability of the material, but these components may affect the biocompatibility and surface properties of the material, thereby increasing the risk of sparingly soluble salt deposition. The present invention reduces the use of hydrophobic acrylate monomers and instead uses 2-methacryloyloxyethyl phosphorylcholine as a key component. 2-Methacryloyloxyethyl phosphorylcholine has strong hydrophilicity and good biocompatibility, can effectively improve the surface properties of the material, make it less likely to combine with calcium ions, and reduce the possibility of calcium salt deposition. Specifically, 2-methacryloyloxyethyl phosphorylcholine works through the following mechanisms:

[0046] Improved hydrophilicity: The hydrophilic group of 2-methacryloyloxyethyl phosphorylcholine can increase the surface hydration of the intraocular lens and reduce the risk of calcium salt deposition.

[0047] Function of resisting the deposition of insoluble salts: The phosphorylcholine group in the 2-methacryloyloxyethyl phosphorylcholine molecule can produce steric hindrance with the calcium ions and other mineral ions in the eye, reducing the deposition of these ions on the surface of the artificial lens, thereby avoiding the turbidity of the lens surface.

[0048] By optimizing the material structure, the present invention can significantly reduce the risk of insoluble salt deposition and improve the long-term transparency and stability of the intraocular lens.

[0049] 3. Enhanced biocompatibility and transparency. The biocompatibility of artificial lenses is crucial to their performance after long-term implantation, especially to avoid inflammatory reactions and rejection. 2-methacryloyloxyethyl phosphorylcholine, as a material with excellent biocompatibility, can effectively enhance the affinity of artificial lens materials with intraocular tissues, reduce immune responses, and improve the adaptability of materials in the eye. In addition, the addition of 2-methacryloyloxyethyl phosphorylcholine can optimize the optical properties of the material, maintain its transparency, and prevent the artificial lens from turning yellow or cloudy after long-term implantation, thereby ensuring the patient's vision quality.

[0050] 4. UV absorbers are added. UV absorbers are common ingredients in intraocular lenses, mainly used to absorb and filter ultraviolet rays to protect the eyes from damage by ultraviolet rays. Ultraviolet rays can cause long-term damage to the eyes and may lead to eye diseases such as cataracts and macular degeneration. After adding UV absorbers, intraocular lenses can effectively block the passage of ultraviolet rays and protect the eyes from damage by ultraviolet rays. Especially for elderly cataract patients, the UV filtering function is particularly important. The use of UV absorbers not only improves the functionality of intraocular lenses, but also enhances the patient's postoperative eye health.

[0051] 5. Hydrophilic materials with high water content and high refractive index. The material has a high water content and a higher refractive index, which can maintain the material's excellent high water content, high water absorption expansion coefficient and softness, and maintain the material's high refractive index, which is conducive to the design of thinner and softer artificial lens products.

[0052] 6. The characteristic material with high water absorption expansion coefficient is conducive to the migration of hydration solution in the material, further reducing the risk of deposition of insoluble salts after the material is implanted in the eye, and adjusting the water absorption expansion coefficient of the material through the original material ratio can improve the softness of the material after water absorption and expansion. In addition, high water content and high water absorption expansion coefficient are conducive to improving the image quality of the material processed into artificial lens.

[0053] 7. The production process of the material is simplified. Since the intraocular lens material of the present invention does not need to add complex hydrophobic acrylate monomers, its preparation process is further simplified. The composition and proportion complexity of the material are reduced, which helps to reduce production costs and improve production efficiency. At the same time, the simplified process flow also helps to ensure the quality consistency of the material and reduce the differences between batches, thereby improving the overall quality and reliability of the intraocular lens.

[0054] Therefore, the artificial lens material of the present invention, by virtue of its unique formula and optimized material structure, shows significant advantages in reducing the risk of insoluble salt deposition, improving transparency, enhancing softness and biocompatibility, etc. By reducing the use of hydrophobic components and introducing 2-methacryloyloxyethyl phosphorylcholine components with anti-insoluble salt deposition effects, the present invention effectively solves a series of problems in the prior art, provides patients with a more reliable artificial lens material, improves the postoperative vision recovery effect, and improves the long-term eye health of patients.

[0055] In combination with the first aspect, in some embodiments of the present invention, the content of the acrylate monomer in the preparation raw material is 79.9-92 wt % by mass.

[0056] In the intraocular lens material of the present invention, the content of acrylate monomer is 79.9-92wt%, which ensures the basic mechanical properties of the material. As the main component, acrylate monomer can effectively ensure the mechanical strength and stability of the intraocular lens while providing good biocompatibility. Within this content range, acrylate monomer can effectively enhance the structural integrity of the material, so that it has sufficient strength to adapt to the long-term implantation in the intraocular environment. In addition, the softness and folding performance are also optimized, and the high proportion of acrylate monomer makes the material have good flexibility and operability. Due to the high content of acrylate monomer, the intraocular lens can be folded and pushed more smoothly during the operation, thereby improving the success rate of the operation and reducing the patient's postoperative discomfort. Further, the interference of other ingredients is reduced: the high proportion of acrylate monomer in the formula can ensure its dominant role, reduce the interference of other ingredients such as ultraviolet absorbers and acrylate monomers, make the overall performance of the intraocular lens more stable, and easy to control the final optical and physical properties of the material. Furthermore, the transparency and resistance to insoluble salt deposition are also improved. Although the content of acrylate monomer is relatively high, the combination of UV absorber and acrylate monomer can effectively maintain the transparency of the material. At the same time, the hydrophilicity and resistance to insoluble salt deposition of acrylate monomer ensure the long-term stability of the material after intraocular implantation.

[0057] Therefore, the acrylate monomer content of 79.9-92wt% not only ensures the mechanical properties and flexibility of the material, but also provides the necessary stability for the long-term use of the intraocular lens. At the same time, combined with the optimized design of other components, it effectively reduces the deposition of insoluble salts and opacity.

[0058] In combination with the first aspect, in some embodiments of the present invention, the acrylate monomer includes 2-hydroxyethyl methacrylate.

[0059] In combination with the first aspect, in some embodiments of the present invention, the content of the ultraviolet absorber in the preparation raw material is 2.9-5wt% by mass.

[0060] The content of the ultraviolet absorber in the artificial lens material of the present invention is 2.9-5wt%, which can effectively block ultraviolet rays. The ultraviolet absorber can absorb and filter ultraviolet (UV) radiation, prevent harmful ultraviolet rays from entering the eye, and thus protect the eye from long-term damage caused by ultraviolet rays. Ultraviolet rays are considered to be one of the main factors causing eye diseases such as cataracts and macular degeneration, so the addition of ultraviolet absorbers plays a positive role in preventing these eye diseases. It can also improve eye health and slow down eye aging. Ultraviolet rays are not only harmful to the lens, but also may accelerate the aging process of the eye and cause damage to the intraocular structure. The addition of ultraviolet absorbers can effectively delay this process and help maintain the long-term health of the eyes. Especially for the elderly population, the protective effect of ultraviolet rays is particularly important. Further, the optical properties of the material can also be enhanced. The ultraviolet absorber can improve the optical quality of the artificial lens, avoid the potential impact of ultraviolet rays on the material, and maintain the transparency and optical stability of the lens. Even after long-term implantation, the optical properties of the artificial lens will not degrade due to the influence of ultraviolet rays, thereby providing a clearer visual effect. In addition, the amount of UV absorber can be appropriately increased to increase the refractive index of the material without affecting the water content of the material. Low concentration of UV absorber is effective while reducing side effects. The content of UV absorber is in the range of 2.9-5wt%, which can effectively exert its UV absorption function without affecting other properties of the material. This concentration range ensures the high efficiency of the UV absorption function, while avoiding the adverse effects of excessive UV absorber on other properties of the material (such as transparency, softness, etc.).

[0061] In combination with the first aspect, in some embodiments of the present invention, the ultraviolet absorber includes 2-hydroxy-4-(methacryloyloxy)benzophenone or 2-(4-benzoyl-3-hydroxyphenoxy)ethyl 2-acrylate.

[0062] In combination with the first aspect, in some embodiments of the present invention, the content of 2-methacryloyloxyethyl phosphorylcholine in the preparation raw material is 4.9-15wt% by mass.

[0063] 2-Methacryloyloxyethyl phosphorylcholine is a highly hydrophilic molecule that can significantly improve the hydration of materials and reduce the deposition of insoluble salts (such as calcium salts) on the surface of the lens. The deposition of insoluble salts is one of the important reasons for the turbidity and loss of transparency of intraocular lenses. The addition of 2-methacryloyloxyethyl phosphorylcholine makes the surface of the lens more hydrated, reduces the adhesion of calcium ions and other minerals, and thus effectively reduces the risk of insoluble salt deposition and maintains the long-term transparency of the lens. The phosphorylcholine group in the 2-methacryloyloxyethyl phosphorylcholine molecule has good biocompatibility, can effectively reduce immune rejection reactions, and improve the affinity of the material with intraocular tissues. This makes the implanted intraocular lens more easily accepted by intraocular tissues, reduces the incidence of inflammatory reactions, and improves the stability and comfort of the implant. The addition of 2-methacryloyloxyethyl phosphorylcholine also improves the softness and operability of the material, making the intraocular lens easier to fold and push during surgery. This not only improves the smoothness of the operation, but also reduces potential risks and complications during the operation, and improves the safety of the operation. In addition, 2-methacryloyloxyethyl phosphorylcholine can improve the optical properties of the material and ensure that the intraocular lens remains transparent for a long time. Its hydrophilicity and anti-deposition properties help to delay the process of whitening or turbidity on the surface of the lens, thereby improving the patient's postoperative visual effect and comfort.

[0064] Therefore, 4.9-15wt% of 2-methacryloyloxyethyl phosphorylcholine can significantly enhance the hydrophilicity, water absorption and swelling, resistance to insoluble salt deposition and biocompatibility of the intraocular lens, improve the softness and operability of the material, while maintaining long-term transparency and optical stability, providing patients with more reliable postoperative effects.

[0065] In combination with the first aspect, in some embodiments of the present invention, the content of the initiator in the preparation raw material is ≥ 0.01 wt %.

[0066] In combination with the first aspect, in some embodiments of the present invention, the initiator includes at least one of azobisisobutyronitrile and azobisisoheptanenitrile.

[0067] In combination with the first aspect, in some embodiments of the present invention, the water content of the intraocular lens material is ≥ 30 wt %.

[0068] A higher water content makes the surface of the material more hydrophilic, which helps reduce intraocular inflammatory reactions and improves the compatibility of the material with intraocular tissues. This can effectively reduce the risk of immune rejection, promote faster healing after surgery, and reduce the patient's postoperative discomfort. Hydration can effectively improve the transparency of the intraocular lens and prevent surface turbidity or yellowing due to lack of water. A higher water content can maintain the optical properties of the material and ensure that patients maintain clear vision after long-term use. It is especially important for long-term implanted intraocular lenses to maintain their long-term transparency. In addition, a higher water content makes the intraocular lens softer and easier to fold and push during surgery. This not only improves the smoothness of the operation and reduces the risk of surgery, but also reduces postoperative discomfort and improves postoperative comfort and recovery. It can be understood that materials with higher water content can maintain good hydration and reduce the deposition of calcium salts on the surface of the material. The deposition of insoluble salts is an important reason for the loss of transparency of intraocular lenses. High water content helps to reduce this phenomenon and extend the service life of intraocular lenses. Furthermore, the higher water content makes the material more compatible with the intraocular environment, which can effectively relieve dry eye symptoms and improve the patient's postoperative comfort. Hydration helps reduce postoperative eye dryness and discomfort, especially for patients who wear intraocular lenses for a long time.

[0069] In combination with the first aspect, in some embodiments of the present invention, the hydration expansion coefficient of the intraocular lens material is ≥1.13.

[0070] A higher hydration expansion coefficient indicates that the material can effectively absorb water and adapt to the intraocular environment, which enhances the biocompatibility of the intraocular lens. This good adaptability makes the intraocular lens more compatible with the intraocular tissue, reduces postoperative immune response and rejection, and promotes postoperative healing and comfort. In addition, materials with a higher hydration expansion coefficient can maintain strong hydration, which helps maintain the transparency of the lens. Hydration reduces the risk of calcium salt deposition on the surface of the material, helps prevent turbidity or yellowing, and thus maintains long-term clear vision. For long-term implanted intraocular lenses, a stable hydration state is essential for transparency. Furthermore, a hydration expansion coefficient ≥ 1.13 indicates that the material can expand appropriately after absorbing water, thereby enhancing the softness and operability of the material. The expanded lens is more flexible, which is convenient for folding and injection during surgery, improving the success rate of surgery and reducing the difficulty of intraoperative operation. Furthermore, a higher hydration expansion coefficient makes the material more hydrophilic, thereby reducing the deposition of calcium salts on the surface of the intraocular lens. The deposition of insoluble salts is a key factor that causes the intraocular lens to become cloudy. Materials with high expansion coefficients reduce the possibility of calcium salt deposition by increasing surface hydration, which helps maintain the long-term transparency of the lens. It should be noted that materials with a hydration expansion coefficient ≥ 1.13 can better adapt to changes in temperature and humidity in the eye, thereby reducing stress and deformation of the lens after surgery. This adaptability allows the intraocular lens to maintain a stable shape in the eye, enhancing its reliability and comfort in long-term use.

[0071] In combination with the first aspect, in some embodiments of the present invention, the elongation at break of the intraocular lens material is ≥ 200 wt %.

[0072] A higher elongation at break indicates that the material has better ductility and flexibility under stress. This makes it easier for the intraocular lens to be folded and injected during surgery, improves the smoothness of the surgical operation, and reduces the difficulty of operation caused by the material being too hard. In addition, materials with higher flexibility can adapt to different morphological changes in the eye and reduce postoperative discomfort. A higher elongation at break also means that the material has stronger tensile resistance and toughness, and can withstand greater mechanical stress without easily breaking or breaking. This is particularly important for intraocular lenses, because they may encounter certain mechanical impacts during implantation. The high elongation at break of the material can effectively reduce the rupture or damage caused by external forces and increase its long-term durability in the eye. Furthermore, materials with high elongation at break are usually softer and more compliant with the intraocular environment, which can reduce pressure and friction on intraocular structures and improve biocompatibility. This flexibility helps the stability and comfort of intraocular lenses in the eye, reduces the foreign body sensation or discomfort that may occur after implantation, and enhances the patient's postoperative comfort. It should also be noted that materials with high elongation at break can usually be successfully folded and injected into the eye with a smaller incision. The operability and adaptability of this material make the surgical process simpler, reduce surgical risks, increase surgical success rates, and reduce the patient's recovery time and discomfort after surgery.

[0073] In combination with the first aspect, in some embodiments of the present invention, the elastic modulus of the intraocular lens material is 0.15-0.35 MPa.

[0074] Moderate elastic modulus makes the material have better flexibility and adaptability in the eye, which can better cooperate with the intraocular tissue and reduce discomfort after implantation. This elasticity allows the intraocular lens to easily adapt to the shape and movement of the eyeball, thereby improving the comfort in the eye, reducing the foreign body sensation and pressure, and enhancing the patient's postoperative experience. In addition, a moderate elastic modulus helps to improve the folding performance and operability of the intraocular lens, making it easier to fold during surgery and push it into the eye through a small incision. This elasticity provides greater flexibility for surgery, improves the success rate of surgery and reduces the difficulty of operation. Materials with low elastic modulus are too soft and may cause difficulty in pushing, while materials that are too hard may increase the pressure on the eye. A moderate elastic modulus can achieve the best operational balance. Furthermore, an intraocular lens with a moderate elastic modulus can withstand normal intraocular pressure and dynamic loads in the eye, while not being too rigid to avoid unnecessary pressure on the surrounding eye structures. The moderate elasticity of the material ensures the morphological stability of the intraocular lens in the eye, which helps to maintain clear vision and the long-term function of the material. Furthermore, a moderate elastic modulus gives the material sufficient toughness to withstand the movement of the eyeball and changes in external pressure during long-term use in the eye without becoming fatigued, deformed, or damaged. An elastic modulus that is too low or too high may cause performance degradation of the intraocular lens during long-term use, while an elastic modulus within this range can effectively improve the durability of the material and ensure its long-term stability in the eye. It should also be noted that a more moderate elastic modulus helps to optimize the surface properties of the material, and combined with the hydrophilicity of the material, makes it less likely for calcium salts to deposit on the surface of the lens. This property can maintain the long-term transparency of the lens, prevent the material from becoming turbid or yellowing due to the deposition of insoluble salts, and thus extend its service life.

[0075] In a second aspect, some embodiments of the present invention provide a method for preparing the intraocular lens material of the first aspect of the present invention, comprising the steps of mixing various preparation raw materials and then subjecting them to polymerization reaction.

[0076] It can be understood that the preparation method of the present invention does not require expensive equipment and complex process control, the reaction conditions are not harsh, the raw materials are easily available, the production cost is low, and it is easy to industrialize production.

[0077] In combination with the second aspect, in some embodiments of the present invention, the polymerization reaction temperature is 25-120°C.

[0078] In combination with the second aspect, in some embodiments of the present invention, the polymerization reaction time is 12 hours to 7 days.

[0079] In conjunction with the second aspect, in some embodiments of the present invention, the initiator includes at least one of azobisisobutyronitrile and azobisisoheptanenitrile.

[0080] In a third aspect, some embodiments of the present invention provide use of the hydrophilic intraocular lens material of the first aspect of the present invention in preparing an aphakic intraocular lens or a phakic intraocular lens.

[0081] It should be noted that aphakic intraocular lenses are artificial lenses used to replace the cloudy natural lens in the eye, and are often used for patients whose natural lens has been removed due to cataract surgery, trauma or disease. Phakic intraocular lenses are implanted in the eye to correct refractive errors while retaining the natural lens of the human eye.

[0082] Aphakic intraocular lenses are usually implanted in the natural lens capsule after the natural lens is removed, and usually do not come into contact with other tissues. Phakic intraocular lenses are usually implanted between the natural lens and the iris, and come into contact with the iris, ciliary muscle / sulcus and natural lens, and have higher requirements for aqueous humor diffusion. Therefore, phakic intraocular lenses have higher requirements for the mechanical properties, biological properties, comfort and aqueous humor diffusion of materials.

[0083] Current intraocular lens materials are generally not suitable for use in phakic intraocular lenses for the following reasons.

[0084] Hydrophobic intraocular lens materials and materials with a high content of hydrophobic monomers are usually harder and more sticky, and can easily cut the iris and suspensory ligaments and adhere to the iris, causing pigment deposition problems. They are also not conducive to the diffusion of intraocular solutions, and can easily cause increased intraocular pressure and salt deposition problems. Therefore, such materials are usually only suitable for the preparation of intraocular lenses for the treatment of cataracts, and are not suitable for the preparation of phakic intraocular lenses for correcting refractive errors.

[0085] In terms of flexibility and foldability, phakic patients usually need to implant artificial lenses into their eyes through tiny incisions during surgery. Therefore, the flexibility and foldability of artificial lenses are crucial. Existing materials, especially some hard materials, may not be flexible enough to be flexibly operated during surgery. For artificial lenses designed specifically for phakic patients, the flexibility and foldability of the materials must meet certain standards so that they can be implanted through small incisions.

[0086] The hydrophilic intraocular lens material provided by the present invention can be used not only for preparing aphakic intraocular lenses, but also for preparing phakic intraocular lenses. Specifically, it has at least the following beneficial effects:

[0087] 1. Improve biocompatibility: The artificial lens material of the present invention has high hydrophilicity and biocompatibility, and can effectively reduce immune rejection reactions. Especially when implanted in the eyes of patients with aphakia or phakia, it can be better compatible with intraocular tissues, reduce postoperative discomfort, and improve long-term stability and comfort after implantation.

[0088] 2. Prevent salt deposition: Since the artificial lens material of the present invention has a high water absorption expansion coefficient and strong hydrophilicity, it can reduce the deposition of insoluble salts in the eye, especially calcium salt deposition, thereby reducing the risk of the lens material becoming turbid, extending the service life of the artificial lens, and ensuring the visual effect.

[0089] 3. Ultraviolet protection: By using ultraviolet absorbers, intraocular lens materials can effectively absorb and block ultraviolet rays, protect the eyes from damage caused by ultraviolet rays, and prevent eye diseases such as cataracts. This function is especially important in patients with aphakia and phakia, as it can effectively delay the aging process of the eyes and protect eye health.

[0090] 4. Better refractive index control: The present invention can effectively adjust the refractive index of the material by adjusting the content of the ultraviolet absorber, so that it can still maintain a high refractive index under high water content. This is particularly important for patients or phakic patients who need specific optical power. While ensuring optical performance, it can achieve a thinner and lighter artificial lens design and improve the operability of implant surgery.

[0091] 5. Improve surgical operability and comfort: The material has good flexibility and folding properties, which facilitates surgical operation. After intraocular implantation, the lower elastic modulus makes the intraocular lens more compatible with intraocular tissue, providing higher comfort and stability, and reducing postoperative discomfort.

[0092] 6. Low production cost and easy industrialization: The artificial lens material of the present invention adopts a simple raw material formula and production process, has a low production cost, and does not require complex equipment and harsh conditions during the preparation process. Therefore, it is easy to industrialize production and meet the needs of large-scale clinical applications.

[0093] Therefore, the application of the hydrophilic intraocular lens material of the present invention in aphakic intraocular lenses or phakic intraocular lenses can not only provide excellent optical properties and biocompatibility, but also significantly improve postoperative comfort and long-term stability, and has broad clinical application prospects.

[0094] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.

[0095] In the description of the present invention, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0096] Unless otherwise specified, "room temperature" in the present invention means 25°C±5°C.

[0097] Unless otherwise specified, "about" in the present invention means that the allowable error is within ±5%.

[0098] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.

[0099] The CAS number of 2-hydroxyethyl methacrylate is 868-77-9, abbreviated as HEMA.

[0100] The CAS number of 2-hydroxy-4-(methacryloyloxy)benzophenone is 2035-72-5.

[0101] The CAS number of 2-(4-benzoyl-3-hydroxyphenoxy)ethyl 2-acrylate is 16432-81-8.

[0102] The CAS number of 2-methacryloyloxyethyl phosphorylcholine is 67881-98-5, abbreviated as MPC.

[0103] The CAS number of the initiator azobisisobutyronitrile is 78-67-1, abbreviated as AIBN.

[0104] It should be noted that "wt%" in the text means the mass content percentage (%), and wt is the abbreviation of weight. For example, the water content of the intraocular lens material is ≥30wt%, which means that the mass percentage of water in the intraocular lens material is ≥30%.

[0105] Example 1

[0106] Provided is an artificial lens material, the raw materials for preparation are:

[0107] Hydrophilic monomer 2-hydroxyethyl methacrylate: 92 g (91.99 wt%),

[0108] UV absorber 2-hydroxy-4-(methacryloyloxy)benzophenone: 3 g (2.99 wt%),

[0109] Hydrophilic monomer 2-methacryloyloxyethyl phosphorylcholine: 5 g (4.99 wt%),

[0110] Initiator azobisisobutyronitrile: 0.01 g (0.01 wt%).

[0111] The preparation method is:

[0112] In a sealed cylindrical plastic cavity, 2-hydroxyethyl methacrylate, 2-hydroxy-4-(methacryloyloxy)benzophenone, 2-methacryloyloxyethyl phosphorylcholine and an initiator are mixed and then polymerized. The polymerization temperature is 30° C. and the polymerization time is 7 days.

[0113] Example 2

[0114] Provided is an artificial lens material, the raw materials for preparation are:

[0115] Hydrophilic monomer 2-hydroxyethyl methacrylate: 86 g (85.99 wt%),

[0116] UV absorber 2-acrylic acid-2-(4-benzoyl-3-hydroxyphenoxy)ethyl ester: 4 g (3.99 wt%),

[0117] Hydrophilic monomer 2-methacryloyloxyethyl phosphorylcholine: 10 g (9.99 wt%),

[0118] Initiator azobisisobutyronitrile: 0.02 g (0.02 wt%).

[0119] The preparation method is:

[0120] In a cylindrical plastic cavity, 2-hydroxyethyl methacrylate, 2-hydroxy-4-(methacryloyloxy)benzophenone, 2-methacryloyloxyethyl phosphorylcholine and an initiator are mixed and then polymerized at a temperature of 40° C. for 5 days.

[0121] Example 3

[0122] Provided is an artificial lens material, the raw materials for preparation are:

[0123] Hydrophilic monomer 2-hydroxyethyl methacrylate: 80 g (79.99 wt%),

[0124] UV absorber 2-hydroxy-4-(methacryloyloxy)benzophenone: 5 g (4.99 wt%),

[0125] Hydrophilic monomer 2-methacryloyloxyethyl phosphorylcholine: 15 g (14.99 wt%),

[0126] Initiator azobisisobutyronitrile: 0.05 g (0.05 wt%).

[0127] The preparation method is:

[0128] In a cylindrical plastic cavity, 2-hydroxyethyl methacrylate, 2-hydroxy-4-(methacryloyloxy)benzophenone, 2-methacryloyloxyethyl phosphorylcholine and an initiator are mixed and then polymerized at a temperature of 80° C. for 12 hours.

[0129] Comparative Example 1

[0130] This comparative example contains a hydrophobic monomer and a cross-linking agent, as well as a low-content ultraviolet absorber, and does not contain MPC. Specifically:

[0131] In a cylindrical plastic cavity, 77.6 g (77.59% wt) of 2-hydroxyethyl methacrylate, 21 g (20.99 wt%) of 2-ethoxyethyl methacrylate (CAS No.: 2370-63-0), 1.0 g (0.99% wt) of ultraviolet absorber 2-hydroxy-4-(methacryloyloxy) benzophenone, 0.4 g (0.39 wt%) of crosslinking agent ethylene glycol dimethacrylate (CAS No.: 97-90-5) and 0.05 g (0.05 wt%) of initiator azobisisobutyronitrile were mixed and polymerized at a temperature of 80° C. for 12 hours.

[0132] Comparative Example 2

[0133] This comparative example contains a hydrophobic monomer and a crosslinking agent, as well as a low content of ultraviolet absorber and a low content of MPC. Specifically:

[0134] In a cylindrical plastic cavity, 83.1 g (83.09% wt) of 2-hydroxyethyl methacrylate, 14 g (13.99 wt%) of methyl methacrylate (CAS No.: 80-62-6), 0.5 g (0.49 wt%) of ultraviolet absorber 2-hydroxy-4-(methacryloyloxy)benzophenone, 2 g (1.99 wt%) of 2-methacryloyloxyethyl phosphorylcholine, 0.4 g (0.39 wt%) of crosslinking agent ethylene glycol dimethacrylate and 0.05 g (0.05 wt%) of initiator azobisisobutyronitrile were mixed evenly and polymerized at a polymerization temperature of 80° C. for 12 hours.

[0135] Performance Testing

[0136] The properties of the intraocular lens materials of Examples 1 to 3 and Comparative Examples 1 and 2 were tested, and the results are shown in Table 1.

[0137] The test method for the moisture content of the material is to test according to GB11417.7-2012 method.

[0138] Test method for hydration expansion coefficient and refractive index: The material is milled into an intraocular lens sample and the total diameter D of the dry product is tested. dry (mm), then soak the sample in water at room temperature until the mass is constant, and then measure the total diameter D of the sample wet (mm), expansion coefficient = D wet (mm) / D dry (mm). The refractive index was checked on an Abbe refractometer using the same sample.

[0139] Product image quality testing method: Maintaining the same optical design, the material is turned and milled into artificial lens samples, and the MTF value of the sample is tested using artificial lens optical inspection equipment. The higher the value, the better the image quality.

[0140] The test method for elongation at break and elastic modulus is as follows: the material is turned and milled into dumbbell-shaped samples, and then the samples are immersed in water at room temperature until the mass is constant, and then a universal tensile testing machine is used for tensile testing. During the test, the samples are immersed in water, and the elongation at break and elastic modulus values ​​are output.

[0141] In vitro simulation test method for material whitening phenomenon: the material is turned and milled into an artificial lens sample, the sample is immersed in water at room temperature until the mass is constant, and then the sample is placed in a 0 to 4°C refrigerator for 24 hours, and then the sample is taken out and immersed in 35±2°C water for 1 to 30 minutes to observe whether the sample turns white.

[0142] In vitro salt deposition simulation test: the material was milled into artificial lens samples, immersed in a simulated intraocular equilibrium solution, sealed with vials and rubber stoppers, kept warm at 75°C for 30 days, then placed at room temperature for 7 days, and the sample surface was observed for deposits, and further stained with a dye for observation.

[0143] Table 1

[0144]

[0145] As can be seen from Table 1, the water content of Example 1 (water content 36wt%), Example 2 (water content 40wt%) and Example 3 (water content 45wt%) is relatively high, which helps to enhance the transparency, flexibility and biocompatibility of the material. In contrast, the water content of Comparative Example 1 (water content 26wt%) and Comparative Example 2 (water content 25wt%) is significantly lower, which may result in poor hydrophilicity, transparency, flexibility and biocompatibility of the material.

[0146] The hydration expansion coefficients of Examples 1 to 3 gradually increase, indicating that as the water content increases, the hydration expansion coefficient of the material also increases. This is consistent with the high water absorption expansion coefficient characteristics of the material, which helps to improve the flexibility and comfort of the lens. However, the hydration expansion coefficients of Comparative Examples 1 and 2 are relatively low, which will result in poor softness of the material and affect the stability and comfort of the eye.

[0147] The elastic modulus of the embodiment is significantly lower than that of the comparative example, indicating that it has good softness, while the elastic modulus of comparative examples 1 and 2 is higher, resulting in poor comfort in the eye.

[0148] The image quality (MTF value) of all embodiments and comparative examples is relatively high (0.6 or close to 0.6), indicating that the optical performance of the material is good and meets the transparency requirements. This index reflects the visual effect and clarity of the material in the eye and meets the requirements of long-term use.

[0149] Example 1, Example 2 and Example 3 did not undergo whitening or in vitro simulated salt-free deposition under temperature changes, demonstrating good stability and resistance to insoluble salt deposition.

[0150] Comparative Example 1 showed a whitening phenomenon, indicating that materials with low water content are prone to adverse reactions (such as deposition of insoluble salts) under temperature changes, resulting in whitening, which affects the transparency and long-term use effect of the material.

[0151] Comparative Example 2 did not show the whitening phenomenon, but its performance was still lower than that of Examples 1 to 3, especially in terms of elastic modulus, which was significantly higher, and would affect its biocompatibility and comfort.

[0152] In summary, the high water content and the appropriate hydration expansion coefficient, elongation at break and elastic modulus in Examples 1 to 3 optimize the flexibility and operability of the material, which meets the requirements for intraocular use. Materials with high water content not only improve biocompatibility, but can also effectively reduce calcium deposition, prolong intraocular stability and service life. In contrast, the low water content of Comparative Example 1 causes it to easily deposit calcium (whitening phenomenon), affecting its transparency and long-term stability. Although Comparative Example 2 is not white, its higher elastic modulus and lower water content still limit its overall performance. The artificial lens material of the present invention optimizes the water content, flexibility, transparency and anti-calcium deposition ability of the material by controlling the content of acrylate monomer and 2-methacryloyloxyethyl phosphorylcholine, and significantly improves the surgical operability and long-term stability of the material. The comparative sample with low water content shows poor performance, especially in terms of transparency and comfort, which limits its application prospects.

[0153] The present invention has been described in detail above in conjunction with the embodiments, but the present invention is not limited to the above embodiments, and various changes can be made within the knowledge scope of ordinary technicians in the relevant technical field without departing from the purpose of the present invention.

Claims

1. A hydrophilic intraocular lens material, characterized in that: The preparation raw materials include acrylic acid ester monomer, ultraviolet absorber, 2-methacryloyloxyethyl phosphorylcholine and initiator.

2. The hydrophilic intraocular lens material according to claim 1, characterized in that: In terms of mass percentage, the content of the acrylic acid ester monomer in the preparation raw material is 79.9-92wt%; and / or the acrylic acid ester monomer includes 2-hydroxyethyl methacrylate.

3. The hydrophilic intraocular lens material according to claim 1, characterized in that: In terms of mass percentage, the content of the ultraviolet absorber in the preparation raw material is 2.9-5wt%.

4. The hydrophilic intraocular lens material according to claim 1, characterized in that: In terms of mass percentage, the content of the 2-methacryloyloxyethyl phosphorylcholine in the preparation raw material is 4.9-15wt%.

5. The hydrophilic intraocular lens material according to claim 1, characterized in that: The content of the initiator in the preparation raw material is ≥ 0.01 wt %.

6. The hydrophilic intraocular lens material according to claim 1, characterized in that: The ultraviolet absorber includes 2-hydroxy-4-(methacryloyloxy)benzophenone or 2-(4-benzoyl-3-hydroxyphenoxy)ethyl 2-acrylate.

7. The hydrophilic intraocular lens material according to any one of claims 1 to 6, characterized in that: The water content of the artificial lens material is ≥30wt%; and / or the hydration expansion coefficient of the artificial lens material is ≥1.13; and / or the elongation at break of the artificial lens material is ≥200%; and / or the elastic modulus of the artificial lens material is 0.15-0.35MPa.

8. The hydrophilic intraocular lens material according to any one of claims 1 to 6, characterized in that: The preparation raw materials are 2-hydroxyethyl methacrylate, 2-hydroxy-4-(methacryloyloxy)benzophenone, 2-methacryloyloxyethyl phosphorylcholine and azobisisobutyronitrile, wherein the proportion of 2-hydroxyethyl methacrylate in the preparation raw materials is 91.99wt%, the proportion of 2-hydroxy-4-(methacryloyloxy)benzophenone in the preparation raw materials is 2.99wt%, the proportion of 2-methacryloyloxyethyl phosphorylcholine in the preparation raw materials is 4.99wt%, and the proportion of azobisisobutyronitrile in the preparation raw materials is 0.01wt%; and / or, the preparation raw materials are 2-hydroxyethyl methacrylate, 2-(4-benzoyl-3-hydroxyphenoxy)ethyl 2-acrylate, 2-methacryloyloxyethyl phosphorylcholine and azobisisobutyronitrile, wherein the proportion of 2-hydroxyethyl methacrylate in the preparation raw materials is 85.99wt%, the proportion of 2 -Acrylic acid-2-(4-benzoyl-3-hydroxyphenoxy)ethyl ester accounts for 3.99wt% of the raw materials for preparation, the 2-methacryloyloxyethyl phosphorylcholine accounts for 9.99wt% of the raw materials for preparation, and the azobisisobutyronitrile accounts for 0.02wt% of the raw materials for preparation; and / or, the raw materials for preparation are methacrylate-2-hydroxyethyl ester, 2-hydroxy-4-(methacryloyloxy)benzophenone, 2-methacryloyloxyethyl phosphorylcholine and azobisisobutyronitrile, the methacrylate-2-hydroxyethyl ester accounts for 79.99wt% of the raw materials for preparation, the 2-hydroxy-4-(methacryloyloxy)benzophenone accounts for 4.99wt% of the raw materials for preparation, the 2-methacryloyloxyethyl phosphorylcholine accounts for 14.99wt% of the raw materials for preparation, and the azobisisobutyronitrile accounts for 0.05wt% of the raw materials for preparation.

9. A method for preparing the hydrophilic intraocular lens material according to any one of claims 1 to 8, characterized in that: The method comprises the steps of mixing various prepared raw materials and then performing polymerization reaction; and / or the polymerization reaction temperature is 20 to 120° C.; and / or the polymerization reaction time is 12 hours to 7 days.

10. Use of the hydrophilic intraocular lens material according to any one of claims 1 to 8 in the preparation of an aphakic intraocular lens or a phakic intraocular lens.